14. Chat and Instant Messaging Systems (synchronous): Report 2/ 3 - Kinsel, Ellen; Roy, Merv; Waldman, Harley; Woloschuk, Donna M. M.; Fahy, Patrick J. (International Review of Research in Open and Distributed Learning, 2002)
This study extends the earlier review of online chat systems (Report 6), by reviewing a further seven products that provide text-based instant messaging (IM). The functionality of these products in distance education contexts is stressed in relation to their comparative costs, complexity, control, clarity, technical framework, and other functional options.